Coherent-Incoherent Crossover of Charge and Neutral Mode Transport as Evidence for the Disorder-Dominated Fractional Edge Phase - Hashisaka, Masayuki; Ito, Takuya; Akiho, Takafumi; Sasaki, Satoshi; Kumada, Norio; Shibata, Naokazu; Muraki, Koji (Physical review. X, 2023)
Couplings between topological edge channels open electronic phases possessing nontrivial eigenmodes far beyond the noninteracting-edge picture. However, inelastic scatterings mask the eigenmodes’ inherent features, often preventing us from identifying the phases, as is the case for the quintessential Landau-level filling factor ν=2/3 edge composed of the counterpropagating ν=1/3 and 1 (1/3–1) channels. Here, we study the coherent-incoherent crossover of the 1/3–1 channels by tuning the channel length in situ using a new device architecture comprising a junction of ν=1/3 and 1 systems, the particle-hole conjugate of the 2/3 edge. We successfully observed the concurrence of the fluctuating electrical conductance and the quantized thermal conductance in the crossover regime, the definitive hallmark of the eigenmodes in the disorder-dominated edge phase left experimentally unverified.